Let's pretend this never happened : by Jamie Kelly - Benton, Jim. (Benton, Jim. Dear dumb diary, 2004)
In her diary, middle school student Jamie Kelly describes her life at home and at school, including her attempts to triumph over her nemesis, the beautiful and popular Angeline.